2018
DOI: 10.1029/2018gl079940
|View full text |Cite
|
Sign up to set email alerts
|

Future Changes in Seasonality of the North Pacific and North Atlantic Subtropical Highs

Abstract: The subtropical highs have a zonal mean and a zonally asymmetric component related to the Hadley cell and land‐sea contrast, respectively. Based on 37 Coupled Model Intercomparison Project phase 5 models, relative roles of the Hadley cell and land‐sea contrast in future changes of the North Pacific and North Atlantic subtropical highs (NPSH and NASH) are evaluated. Both the NPSH and NASH are significantly enhanced during boreal spring (April–June) but not in summer (July–September). Although the zonally asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 33 publications
6
39
0
Order By: Relevance
“…Xie et al 2010, Mizuta et al 2014). During boreal summer, the North Pacific High (NPH) weakens (negative ΔSLP) in response to climate warming (figure 1(e); table 1), consistent with CMIP5 ensemble mean response reported in previous studies (He et al 2017, Song et al 2018. In this model, the western North Pacific subtropical high (WNPSH) around the Philippines is enhanced (figure 1(e); table 1), although model responses are divergent among CMIP5 models (He and Zhou 2015).…”
Section: Ar Response To Climate Warmingsupporting
confidence: 83%
“…Xie et al 2010, Mizuta et al 2014). During boreal summer, the North Pacific High (NPH) weakens (negative ΔSLP) in response to climate warming (figure 1(e); table 1), consistent with CMIP5 ensemble mean response reported in previous studies (He et al 2017, Song et al 2018. In this model, the western North Pacific subtropical high (WNPSH) around the Philippines is enhanced (figure 1(e); table 1), although model responses are divergent among CMIP5 models (He and Zhou 2015).…”
Section: Ar Response To Climate Warmingsupporting
confidence: 83%
“…In contrast to the RC edge, the subtropical ridge (see Figures c, d, g, h, S3c, S3d, S3g, and S3h) shifts poleward almost uniformly over the SH year round in a warming climate, even at longitudes where no RC is defined (e.g., the South Central Pacific during JJA; Song et al, ); in some cases, the SLP signal may reflect changes in the eddy‐driven jet rather than the RC (Pena‐Ortiz et al, ). Our results suggest that caution should be exercised when interpreting the zonal mean SH climate change response; traditionally, the strong HC widening signal over the SH is ascribed in part to the reduced land‐sea contrast over the SH and a more zonally symmetric circulation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, increased atmospheric moisture in this pattern leads to more extreme precipitation over the central US in a warmer climate. Song et al (2018) found that the North Atlantic Subtropical High (NASH) and North Pacific Subtropical High (NPSH) strengthen more in spring than summer under future warming. Associated with the enhancement of the Great Plain low level jet and northward shift of the NASH in spring, precipitation is enhanced over the northern Great Plains and northeastern US.…”
Section: Projections Of Future Lsmp Behavior Associated With Precipitmentioning
confidence: 99%